2021
DOI: 10.1088/1757-899x/1097/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Model Detail Level on the Prognosis Quality of the Perceived Sound of an Electrified Passenger Car Powertrain

Abstract: Complex and resource intensive multi-physical models which integrate the domains of electrotechnical, structural dynamics and acoustics are needed to predict the noise, vibration and harshness (NVH) behavior of an electric passenger car drive train. Because of the highly limited resources in product development process of cars, engineers request efficient models with a good balance between accuracy and model creation as well as calculation effort. Knowing about which components and effects influence the progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Moreover, psychoacoustic models and their ability to predict changes in perceived MOTC are referenced (Doleschal et al, 2021). Drichel et al (2021) suggested an efficient prediction model for EV-NVH behavior and investigated the influence of its model fidelity level on the predictive quality of the perceived drivetrain-related airborne noise while considering human perception. The model development itself included the analyses of the psychoacoustic metrics loudness, sharpness, tonality, roughness, and psychoacoustic annoyance, which led Drichel et al (2021) to the following observations: additional sidebands and friction-related excitations made the stimuli sound less tonal; more broad-band noise led to higher 1 Please note that these findings are conducted from the article's English abstract only, whereas the article of Fang et al (2015) itself was written in Chinese and not available to us in English language in an authorized version.…”
Section: Results Of the Research Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, psychoacoustic models and their ability to predict changes in perceived MOTC are referenced (Doleschal et al, 2021). Drichel et al (2021) suggested an efficient prediction model for EV-NVH behavior and investigated the influence of its model fidelity level on the predictive quality of the perceived drivetrain-related airborne noise while considering human perception. The model development itself included the analyses of the psychoacoustic metrics loudness, sharpness, tonality, roughness, and psychoacoustic annoyance, which led Drichel et al (2021) to the following observations: additional sidebands and friction-related excitations made the stimuli sound less tonal; more broad-band noise led to higher 1 Please note that these findings are conducted from the article's English abstract only, whereas the article of Fang et al (2015) itself was written in Chinese and not available to us in English language in an authorized version.…”
Section: Results Of the Research Analysismentioning
confidence: 99%
“…Frontiers in Mechanical Engineering frontiersin.org roughness; noise components in higher frequency ranges led to higher sharpness scores as the simulation might have underestimated the SPL in these ranges. For the validation of the model N = 30 participants were asked to evaluate multiple noise stimuli concerning a reference in regards to their similarity (from 0 = completely dissimilar to 100 = absolutely identical) in a MUSHRA test (Multi-Stimulus Test with Hidden Reference and Anchor) (Drichel et al, 2021). Table 1 gives an overview of the summarized literature assigned to this cluster and its analyzed parameters: a total of 16 articles, seven of them also including a comparison with subjective data.…”
Section: Results Of the Research Analysismentioning
confidence: 99%